Geometrical Pedagogy of Polygons: Multidimensional Calculation Of Cubic Structures - Peddintia, Sirisha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
We will see many things from the start to the end of the day. Large buildings, vehicle mortars, notebooks, and mechanical pumping machines. All these things have some polygons embedded in them. Everything in the world works with geometry; in physics, the inclined plane scenario, and in chemistry, the structural bonds and chemical bonds all require polygons like cubes and cuboids to perform the job to the fullest. So in this research paper, we will discuss the various types of cubical polygons. We will be going deep with their structures and physics properties. This research paper focuses on more than 3- dimensional cubic figures, and it can be a foundation for future inventions.